A Dramatic Analysis of Montage: Exploring the Style and Language of Ophelia Alcantara-Dimalanta's Montage (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This  study  presents  a  dramatic analysis  of Ophelia Alcantara-Dimalanta‟s  Montage  by providing a syntactic and lexical investigation of the poem. It attempts to investigate the style and the language of the poem by focusing on the overall structure of the poem and the grammatical structure of the sentences thereby leading to a deeper understanding of the text. The analysis focusesn the syntax, specifically the structure of sentences, and the vocabulary of the poem. Some pedagogical implicationsre then drawn towards the concluding remarks of the study.